COMPUTERIZED SUPPORT IN ENGLISH TEACHING - Matkarimova , Mashhura Madiyor qizi; Ziyadullayeva Aziza Akmalovna (GOLDEN BRAIN, 2024)
This article discusses how can computers make learning English effectively. The use of modern technology in English classes is a very important part of system, which is necessary for the development of interest in the English language and information technology itself, by expanding ideas about the fields of application of computers and computer science methods.Computerized support in English teaching